Analisis Kualitas Website Gramedia Terhadap Kepuasan Pengguna Menggunakan Metode WebQual 4.0 - Adhitia Bagas Pratama; Almy Rizki Akbar; Rafael Syafiq (PT Jurnal Cendekia Indonesia, 2025)
This study aims to analyze the quality of the Gramedia website and its impact on user satisfaction using the WebQual 4.0l method. The research method employed is descriptive quantitative, with data collected through digital questionnaires distributed to 14 active users. The research instrument was measured based on three main WebQual 4.0 dimensions: usability, information quality, and service interaction quality. The results indicate that the Gramedia website maintains high-quality standards, with the accessibility (usability) dimension achieving the highest score (64.4%). Furthermore, 85.7% of respondents expressed satisfaction with the service interaction, and 78.6% regularly engage in shopping transactions. However, the aspect of information accuracy requires slight optimization regarding real-time stock data synchronization. Overall, the quality of the Gramedia website has successfully met user expectations and functions effectively as a digital literacy solution.